Strengthening Character Education Based on Ethnic Advantage through Higher Education Curriculum Integration in the Industrial Revolution Era 4.0 - Carolina M. Lasambouw; Neneng Nuryati; Ediana Sutjiredjeki; Ajeng Ayu Milanti; Florida Mathilda (Graduate School of Universitas Negeri Malang, 2023)
Strengthening character education in the era of the industrial revolution 4.0 is urgent to anticipate the dehumanization of students. This research using exploratory qualitative methods has found seven superior ethnic characteristics in Indonesia as the most dominant: independent, consistent, hardworking, honest, challenging, assertive, and happy to work together. This paper describes the framework for strengthening character education by integrating prominent ethnic characters in Indonesia with the characters that become learning outcomes in national compulsory courses and skills courses in the higher education curriculum. As a result, student achievement in character aspects asses in an integrated manner at the end of the semester.